Rancang Bangun Aplikasi UMKM Obat Tradisional Kalimantan Tengah berbasis Android - Novanti, Anastia Ivanabilla; Sari, Nova Noor Kamala (Universitas Palangka Raya, 2021)
Central Kalimantan is known for its diversity of local plants. Moreover, most of these plants are also known for their health benefits. This is a great opportunity for the community to process these plants into traditional medicines and establish Micro, Small and Medium Enterprises (MSMEs) selling traditional medicines. Unfortunately, these MSME entrepreneurs are not widely introduced to the surrounding community so that people also experience difficulties when they want to find traditional medicine. The Android-based Central Kalimantan Traditional Medicine Search Information System application was created so that users who are local people can search for traditional medicine stores selling the medicine they want, view information and be able to see the location of the store. The software system development method used is waterfall through five stages, namely analysis, design, implementation / coding, testing and support. The software developed in the preparation of this Professional Program uses the Java language and uses the Android studio software as a means of application development. MySQL is used as a database storage media about traditional medicine store information. The final result of this research is to produce an android-based application that can be used by the community to search for traditional medicine shops in Central Kalimantan based on keywords of medicine types, as well as helping MSMEs to run their businesses